2015
DOI: 10.3402/meo.v20.26893
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian medical students’ perceptions of expert versus non-expert facilitators in a (non) problem-based learning environment

Abstract: BackgroundIn problem-based learning (PBL), the facilitator plays an important role in guiding the student learning process. However, although content expertise is generally regarded as a useful but non-essential prerequisite for effective PBL facilitation, the perceived importance of content knowledge may be subject to cultural, contextual, and/or experiential influences.AimWe sought to examine medical students’ perceptions of subject-matter expertise among PBL facilitators in a region of the world (Brazil) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
19

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 34 publications
(47 reference statements)
0
22
0
19
Order By: Relevance
“…Couto, et.al found that "subject matter expert" is very good at building knowledge (confirmed by 95% out of 252 students and assisting in generating self-study learning goals (confirmed by 87% of the subject). It shows that tutors with subject-matter expertise are very instrumental in making sure that students identify the correct learning goals [16]. The role of tutors, including how various styles of tutoring affect the success of PBL tutorial have been researched.…”
Section: Results and Analysismentioning
confidence: 99%
“…Couto, et.al found that "subject matter expert" is very good at building knowledge (confirmed by 95% out of 252 students and assisting in generating self-study learning goals (confirmed by 87% of the subject). It shows that tutors with subject-matter expertise are very instrumental in making sure that students identify the correct learning goals [16]. The role of tutors, including how various styles of tutoring affect the success of PBL tutorial have been researched.…”
Section: Results and Analysismentioning
confidence: 99%
“…Brazilian medical students where the overwhelming majority of students reported that content experts were more effective in facilitating their learning process (Couto, Bestetti, Restini, Faria, & Romão, 2015). In contrast, a Canadian study on small group teaching using a prospective randomised trial approach found that, in addition to higher academic performance, students who were taught by process experts were significantly more satisfied with the learning process in the structured small group learning environment (Peets, Cooke, Wright, Coderre, & McLaughlin, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Ainda de acordo com pesquisas de Couto et al 12 , professores que atuaram como facilitadores no método ABP, apro-veitando as diversas ideias e interesses na resolução de problemas pelos alunos e não apenas se limitando a estudos de casos teóricos, obtiveram resultados excelentes em se tratando de conteúdo de aprendizagem. Desse estudo participaram 252 alunos do curso de Medicina do quinto ao oitavo ano, com média de idades de 23,4 anos; 95% deles aprovaram plenamente os procedimentos de aprendizagem, classificando o método -com um tutor especializado que domina a área de conhecimento da matéria discutida em tutorias -como muito bom na construção do conhecimento; somente 16 estudantes (6%) concordaram similarmente quando a mesma matéria discutida em tutorias tinha um não especialista como facilitador (p < 0,0001).…”
Section: Discussionunclassified